Avoidance of the NLRP3 Inflammasome by the Stealth Pathogen, Coxiella burnetii. Issue 4 (July 2021) - Delaney, Martha A.; Hartigh, Andreas den; Carpentier, Samuel J.; Birkland, Timothy P.; Knowles, Donald P.; Cookson, Brad T.; Frevert, Charles W.
Coxiella burnetii, a highly adapted obligate intracellular bacterial pathogen and the cause of the zoonosis Q fever, is a reemerging public health threat. C. burnetii employs a Type IV secretion system (T4SS) to establish and maintain its intracellular niche and modulate host immune responses including the inhibition of apoptosis. Interactions between C. burnetii and caspase-1-mediated inflammasomes are not fully elucidated. This study confirms that C. burnetii does not activate caspase-1 during infection of mouse macrophages in vitro. C. burnetii –infected cells did not develop NLRP3 and ASC foci indicating its ability to avoid cytosolic detection. C. burnetii is unable to inhibit the pyroptosis and IL-1β secretion that is induced by potent inflammasome stimuli but rather enhances these caspase-1-mediated effects. We found that C. burnetii upregulates pro-IL-1β and robustly primes NLRP3 inflammasomes via TLR2 and MyD88 signaling. As for wildtype C. burnetii, T4SS-deficient mutants primed and potentiated NLRP3 inflammasomes. An in vivo model of pulmonary infection in C57BL/6 mice was developed. Mice deficient in NLRP3 or caspase-1 were like wildtype mice in the development and resolution of splenomegaly due to red pulp hyperplasia, and histologic lesions and macrophage kinetics, but had slightly higher pulmonary bacterial burdens at the greatest measured time point. Together these findings indicate that C. burnetii primes but avoids cytosolic detection by NLRP3 inflammasomes, which are not required for the clinical resistance of C57BL/6 mice. Determining mechanisms employed by C. burnetii to avoid cytosolic detection via NLRP3 inflammasomes will be beneficial to the development of preventative and interventional therapies for Q fever.